Causal Determinism and Moral Responsibility - Prašević, Nedžib M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
In the debate between incompatibilists and compatibilists regarding the relationship between causal determinism, moral responsibility, and free will, causal determinism is identified as a potential basis for an excusing argument against moral responsibility. If this were valid, incompatibilists would have a powerful argument for their position, thereby shifting the burden of proof onto the opposing side. However, Strawson and Frankfurt, through their analysis of the role of excuses, have argued why causal determinism cannot serve as an exculpatory basis for responsibility. In this paper, by analyzing their arguments and viewpoints, I aim to examine whether their conclusions are compelling, and whether they allow for a form of Frankfurt-style compatibilism that accepts the possibility of moral responsibility in a world where the thesis of causal determinism holds true.
Keywords: causal determinism; moral responsibility; free will; Strawson; Frankfurt’s example; excuse